A Conceptual Framework for Planning Road Digital Twins - Munkhbaatar Buuveibaatar; Ioannis Brilakis; Matt Peck; George Economides; Wonhee Lee (Buildings)
Digital twin (DT) is an emerging technology gaining traction across various industries. However, its development and application in the architecture, engineering, and construction (AEC) industry remain in their early stage, lagging considerably behind other sectors. This is primarily attributed to the challenges facing the AEC industry, including digital transformation and the lack of formal standards for DT implementation. This study aims to contribute to the conceptualization of DT planning—the early stage of the DT lifecycle—focusing on the road transportation sector, particularly road physical twin planning within the AEC industry. To achieve this, we reviewed the relevant literature defining DT planning. We also examined stakeholders’ relevant guidelines and documents from national bodies that roadmap the road DT planning process to understand the scope and identify knowledge gaps. Based on the findings, mapping the existing road planning process to the constituents of road DT planning was performed for the applicable planning steps. Finally, we proposed a five-layered road DT planning framework that will roadmap future implementations comprising data acquisition, data processing, data modeling and algorithms, data analysis and control, and a service layer plus users. In addition, a case study is incorporated to validate the feasibility of the framework toward applying it further in practice.